2020
DOI: 10.1155/2020/6938620
|View full text |Cite
|
Sign up to set email alerts
|

Cathepsin K Deficiency Impaired Ischemia-Induced Neovascularization in Aged Mice

Abstract: Background. Aging is a major risk factor for cardiovascular disease. Cysteine protease cathepsin K (CatK) has been implicated in the process of angiogenesis, but the exact roles of individual CatK in vessel formation during aging are poorly understood. Methods and Results. To study the putative role of CatK in ischemia-induced angiogenesis, we applied a hindlimb ischemia model to aged wild-type (CatK+/+) and CatK-deficient (CatK−/−) mice. A serial laser Doppler blood-flow analysis revealed that the recovery of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…CTSK is involved in ECM remodeling [ 41 , 92 ], and our results from balicatib-mediated blockage of CTSK activity resulted in increased ECM proteins. To understand the role of CTSK in ECM remodeling, we studied the effects of AdCTSK on the distribution and levels of ECM proteins.…”
Section: Resultsmentioning
confidence: 71%
“…CTSK is involved in ECM remodeling [ 41 , 92 ], and our results from balicatib-mediated blockage of CTSK activity resulted in increased ECM proteins. To understand the role of CTSK in ECM remodeling, we studied the effects of AdCTSK on the distribution and levels of ECM proteins.…”
Section: Resultsmentioning
confidence: 71%
“…Aging has been shown to cause a harmful change in BM‐derived stem cell functions. 15 , 17 , 33 As shown in Figure 5A and 5B , the numbers of TUNEL + cells were lower in the BM‐derived integrin‐α + cells of YBMT mice compared with the non‐YBMT mice. We observed that the numbers of Pax7 + cells were higher in the both muscles of the YBMT mice compared with the control mice ( Figure 5C ).…”
Section: Resultsmentioning
confidence: 89%
“…The use of double immunofluorescence revealed that compared with the muscles of control mice, the soleus and gastrocnemius muscles of the YBMT mice exhibited a diffuse and strong positive staining signal for desmin ( Figure 4A), suggesting that BM‐MSCs might contribute to skeletal muscle regeneration. Aging has been shown to cause a harmful change in BM‐derived stem cell functions 15,17,33 . As shown in Figure 5A and 5B, the numbers of TUNEL + cells were lower in the BM‐derived integrin‐α + cells of YBMT mice compared with the non‐YBMT mice.…”
Section: Resultsmentioning
confidence: 90%
“…Recent multicenter studies have demonstrated that by degrading the extracellular matrix and interacting with VEGF, Cats play important roles in angiogenesis [ [36] , [37] , [38] , [39] , [40] ]. In one study, it was discovered that CatK gene knockout could impair the regeneration of blood vessels in old mice; another report showed that CatL levels and tumor blood vessel regeneration are directly and closely related [ 36 , 37 ]. Together, these studies indicate that Cats might contribute to the process of blood vessel regeneration, although the specific mechanism remains uncertain.…”
Section: Cats Are Involved In All Phases Of Stent-related Restenosismentioning
confidence: 99%